Household food security and nutritional status of preschoolers in Valderrama, Antique - Braga, Mayet Ann; Gordon, Cyrus John G.; Guisihan, Thanz Pamela G.
This study is a cross-sectional survey of 138 randomly selected households from ten (10) similarly randomly-selected barangays in Valderrama, Antique. This study aimed to determine household food security and nutritional status of pre-schoolers in Valderrama, Antique.